(untitled) (Texas Journal of Engineering and Technology, 2024)
The mechanical properties of textile fabrics show their response to various forces. And these forces are different, they can be big or small, and they can act once or repeatedly. During the production and finishing processes of textile yarns, and especially when using them, the structure of yarns changes and their properties gradually deteriorate. This process is called aging of gases. As a result of wear and tear, gases are eroded. If the surface of the gas is completely eroded, the erosion in this case is called general erosion. If the surface of the gas is partially eroded, the erosion in this case is called in situ erosion. General decay completely disables items. This article discusses the mechanical properties of textile materials and their indicators of resistance to decay.